Salicin from host plant as precursor of salicylaldehyde in defensive secretion of Chrysomeline larvae - Pasteels, Jacques M.; Rahier, Martine; Braekman J. C.; Dupont A. (My University, 1983)
Phratora vitellinae L. and Chrysomela tremulae F. (Chrysomelinae, Coleoptera) feed on Salix or Populus spp. (Salicaceae). Their larvae, as well as the larvae of other chrysomelines feeding on Salicaceae, secrete salicylaldehyde. In this study, we demonstrate that salicylaldehyde is derived from salicin, a phenylglucoside present in the leaves of the host plant. The concentration of salicylaldehyde in the secretion is positively correlated with the amount of salicin in the food of the larvae. The transformation of salicin into salicylaldehyde occurs in the defence glands since the β-glucosidase activity is 4 times higher in their glands than in the gut. The larvae recover most of the glucose that results from the hydrolysis of salicin. For generalist predators, such as ants, salicylaldehyde is a more potent deterrent than saligenin or salicin.
Keywords: Chrysomelidae larvae; Phratora vitellinae; Chrysomela tremulae; C.populi; Salix; Populus; salicin; salicylaldehyde; defensive secretion